Colonial Records of the State of Georgia Volume 30: Trustees Letter Book, 1738-1745 - Sweet, Julie Anne (Georgia Open History Library, 1985)
The Colonial Records of the State of Georgia document the colony through its first twenty-five years and includes correspondence between Georgia founder James Oglethorpe and the Trustees for Establishing the Colony, as well as records pertaining to land grants; agreements and interactions with Indigenous peoples; the settlement of a small Jewish community and the Salzburgers, German-speaking Protestant refugees; and the removal on restrictions of land tenure, rum, and slavery in the colony. Most of the local records of colonial Georgia were destroyed during the Revolution. Under Governor James Wright's direction, merchant John Graham loaded much of the official records on his vessel in the Savannah River. During the Battle of the Rice Boats in March 1776, the Inverness was burned while it lay at anchor. The destructive civil war that occurred in the latter phases of the Revolution resulted in further destruction. The Colonial Records of the State of Georgia, drawn from archival material in Great Britain, remain a unique source. Volume 20 concerns the actual founding of Georgia and covers the years 1732-35. It provides background on the settlement and a great deal about the arrival of the colonists and the conditions that they found. Volume 27, spanning the years 1754-56, contains the papers of Georgia's first governor, John Reynolds, as well as the correspondence of various inhabitants. Volume 28, Part I, contains the papers of governors John Reynolds, Henry Ellis, and James Wright from 1757 to 1763. Volume 28, Part II includes the papers of Governor James Wright, acting governor James Habersham, and others. Volume 29 contains the Trustees' Letter Book, 1732-1738. Volume 30 contains the Trustees' Letter Book, 1738-1745 Volume 31 contains the Trustees' Letter Book, 1745-1752 Volume 32 includes entry books of commissions, powers, instructions, leases, grants of land, and other documents by the Trustees.